Emotional Intelligence in Autism - Drigas, Athanasios; Sideraki, Angeliki (Technium Social Sciences Journal, 2021)
Emotional intelligence is a term, which includes various abilities and skills, which enable a person to perceive and handle emotional situations both his own and those of other individuals with the aim of his social and personal development. More specifically, the first part of this work presents an analysis of the role of emotional intelligence in the individual. Then, the 8 pillars of metcognition are mentioned, the role of humor in EI, taking distances with the help of EI, the correlation with hormones, the mindfulness model, the new layered model on EI, and the EI in gifted individual. In the second part, the literature review focuses on the role of EI in autism, the views of Kanner and Aspenger, the expression and understanding of emotions of people with ASD through EI, the mindfulness and the use of robots in autism.